An Exploration of English Song-Based Learning in Developing Young Learners’ Speaking Skills in an Islamic Primary School - Sufya Nadiya; Zainuddin Zainuddin; Nina Agus Hariati (Journal of English Language and Education, 2026)
This study explores the implementation of English song-based learning in developing young learners’ speaking skills at MI Kholafiyah Syafi’iyah Zainul Hasan Genggong. Speaking is challenging because English functions as a third language after Indonesian and Arabic in the dormitory environment, influencing students’ vocabulary, pronunciation, and confidence. This qualitative exploratory study involved three teachers and 37 students. Data were collected through classroom observations conducted over two months, interviews, and documentation, and analyzed using thematic analysis with data triangulation. The findings reveal that teachers use familiar songs whose lyrics are modified with English vocabulary and simple moral values aligned with the Islamic school context. This strategy improves students’ pronunciation, vocabulary, fluency, and confidence while creating an engaging and low-anxiety classroom atmosphere. Therefore, English song-based learning is an effective strategy for developing young learners’ speaking skills.